the being and the essence since thomas aquinas and francisco suárez: between realism and idealism? - Caviglia Marconi, Alessandro Carlo (2022)
This article uses the tension between the unconditioned and the conditioned that Kant detects in the human being and that he presents in the Critique of Pure Reason in order to account for the internal dynamics of the philosophy of religion. In this sense, the work presents the way in which Kant leaves behind dogmatic metaphysics to give way to another, which is the result of the "constriction of reason". Next, the ways in which an attempt is made to condition the unconditioned are presented, both in the case of freedom, in that of thought and in that of spiritual life. The solution to the problem that Kant detects is offered in the abandonment of rational theology and the passage to the resources of critical philosophy, phenomenology, pragmatism or critical theory.